2018
DOI: 10.3892/or.2018.6821
|View full text |Cite
|
Sign up to set email alerts
|

miR‑101 regulates the cell proliferation and apoptosis in diffuse large B‑cell lymphoma by targeting MEK1 via regulation of the ERK/MAPK signaling pathway

Abstract: MAPK kinase 1 (MEK1) is an upstream protein kinase of extracellular signal regulated kinase (ERK), which activates the ERK/MAPK (mitogen activated protein kinase) pathway. Importantly, bioinformatic analysis has shown that there is a target complementary binding site between miR-101 and MEK1. The present study aimed to ascertain whether or not miR-101 plays a role in regulating MEK1 expression, ERK/MAPK pathway activity, and the proliferation and apoptosis in a diffuse large B cell lymphoma (DLBCL) cell line. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Gauthier et al (96) found that the ERK1/2 signalling pathway is involved in cell survival following intestinal injury, and inhibition of this pathway can promote the apoptosis of intestinal injury cells. Huang et al (97) found that blocking the ERK/MAPK signalling pathway inhibited the proliferation of a diffuse large B cell lymphoma cell line and promoted cell apoptosis. Inhibiting the expression of the ERK/MAPK signalling pathway to inhibit tumour cell proliferation may involve inhibition of the cell cycle (98).…”
Section: Erk/mapk Signalling Pathway and Tumorigenesismentioning
confidence: 99%
“…Gauthier et al (96) found that the ERK1/2 signalling pathway is involved in cell survival following intestinal injury, and inhibition of this pathway can promote the apoptosis of intestinal injury cells. Huang et al (97) found that blocking the ERK/MAPK signalling pathway inhibited the proliferation of a diffuse large B cell lymphoma cell line and promoted cell apoptosis. Inhibiting the expression of the ERK/MAPK signalling pathway to inhibit tumour cell proliferation may involve inhibition of the cell cycle (98).…”
Section: Erk/mapk Signalling Pathway and Tumorigenesismentioning
confidence: 99%
“…Considering the important role of the MAPK signaling pathway in lymphomas (47,48) and that the JNK signaling pathway is a well-known pathway that induces cell apoptosis (49), the present study investigated the molecular mechanism by which sCD40L induces apoptosis in lymphoma cell lines. The results demonstrated that the phosphorylation level of JNK was significantly increased, while the phosphorylation level of p38 and ERK did not change following Raji and CA46 cells being treated with sCD40L.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-101 was reported to target mitogen-activated protein kinase kinase 1 (MEK1), an upstream protein kinase of Erk, in DLBCL. The decreased level of miR-101 predicts poorer prognosis of DLBCL patients (43). lncRNA PANDA was found to negatively regulate MAPK/Erk signaling pathway in DLBCL cells (46).…”
Section: Ncrnas Regulate Key Signaling Pathways Associated With Cell mentioning
confidence: 98%